TRANSITIVITY ANALYSIS OF NEWS REPORTS: A CASE OF PARIS ATTACKS REPORTED IN DAILY MAIL AND THE NEW YORK TIMES - Lestari, Fiksi Relita Padma (2016)
Surat kabar mengemas suatu berita secara berbeda-beda. Hal ini dapat menimbulkan makna dan interpretasi yang berbeda pula bagi setiap pembacanya. Studi ini bertujuan untuk mengungkap makna yang terkandung di dalam media berita bernama Daily Mail dan The New York Times terhadap suatu pemberitaan mengenai penyerangan di Paris sebagai suatu contoh bagaimana media membingkai suatu laporan berita. Studi ini secara spesifik berfokus pada analisis proses dominan beserta maknanya pada media berita Daily Mail dan The New York Times. Dalam menganalisis data, studi ini bersifat kualitatif dan menggunakan teori Tata Bahasa Fungsional, Transitivitas, dari Halliday (2004). Hasil yang ditemukan adalah terdapat proses dominan yang berbeda pada kedua media berita tersebut. Dalam merpresentasikan penyerangan di Paris, laporan berita Daily Mail didominasi oleh Proses Vebal (41,28%) dengan cara mengedepankan Perdana Menteri Inggris sebagai Sayer dominan yang sebagian besar membicarakan mengenai rasa empatinya terhadap Prancis (Paris). Sebaliknya, dalam merpresentasikan penyerangan di Paris, laporan berita The New York Times didominasi oleh Proses Material (50,27%) dengan cara mengedepankan penyerang sebagai aktor utama dibalik kekacauan di Paris. Studi ini diharapkan dapat bermanfaat bagi para peneliti lain yang tertarik untuk mengkaji penggunaan bahasa di media berita dan menyadarkan pembaca agar lebih kritis dalam menerima suatu berita. Kata Kunci: Tata Bahasa Fungional, Transitivitas, Laporan Berita News reports frame news in different ways which lead to different meanings and readers' interpretation. The present study attempts to reveal the meanings projected in Daily Mail and The New York Times on the Paris attacks issue to provide an example of how news media frame their reports. This study more specifically focuses on investigating the dominant processes found in Daily Mail and The New York Times news reports and examining the meanings of those dominant processes. The data are four news reports taken from Daily Mail and The New York Times. To analyze the data, this study uses qualitative design and employs Hallidayan (2004) Systemic Functional Grammar, specifically Transitivity. The analysis shows that there is a clear difference in the dominant processes used in the two news media. Daily Mail news reports mostly represent the event at the level of Verbal Process (41.28%). However, The New York Times news reports mostly represent the event at the level of Material Process (50.27%). These dominant processes convey different meanings. The former tends to represent the attacks by foregrounding the Prime Minister of the U.K.as the dominant sayer who mostly talks about the U.K.'s empathy for France. Meanwhile, the latter tends to represent the attacks by foregrounding the attackers as the dominant actors who cause the riot. This study provides significance for making a better news report, giving insight for those who want to conduct studies in Linguistics or news media, and improving the readers to be more critical. Keywords: Systemic Functional Grammar, Transitivity, News Reports